Pelibatan Kaum Cina dalam Sektor Awam di Malaysia - bin Embi, Muhammad Ali; bin Rasimin, Abdul Hadi (Jurnal Demokrasi, 2006)
The Chinese involvement in Malaysia Public Sector is quite small compared to the Malays group.Â  Like other Chinese in South-East Asia, Malaysian Chinese are more likely to get involved in business sector rather than in public sector.Â  Although they are outnumbered by Malays in public sector but in some prestigious profession such as doctor, accountant and engineer the Chinese representation are much better than the Malays. Kata Kunci: Pelibatan, kaum cina, sektor awam, Dasar Ekonomi Baru